Impact of cyclone Tauktae on fishermen’s livelihoodin Karnataka: A climate change perspective analysis: Impact of cyclone Tauktae: A climate change perspective analysis - Gills, Reshma; Bindu Sulochanan; Shelton Padua; D. Ajay Nakhawa; P. Abdul Azeez; L. Loveson Edward; Reeta Jayasankar; Veena Shettigar; Thakurdas; Suresh Kumar Pilli; T. V. Ambrose (Indian Journal of Fisheries, 2024)
The Arabian Sea, off India’s west coast, is undergoing significant changes due to global climate change driven by rising greenhouse gas emissions and warming waters. This is well evidenced by the increasing frequency of cyclonic events along the coast, with five of the eight cyclones recorded in India since 2019 impacting the west coast. Cyclone Tauktae of 2021 was one of the most severe, with extremely recent cyclonic storms wreaking havoc on India’s southern maritime states. This paper examines the extent of damage that happened to households and livelihood-supporting assets, the socio-economic impacts, the social security challenges faced and the preparedness status in Karnataka’s coastal districts. This study also highlights the socio-ecosystem changes that occurred, as well as the coping strategies used in the maritime state of Karnataka in the context of climate change and proposes strategic action plans aimed at effectively mitigating the impacts of tropical cyclones. Keywords: Impact analysis, Socio-economic impact, Socio-ecosystem changes, Tropical cyclones